Análise populacional de colônias de Polybia (Myrapetra) paulista (Ihering, 1896) (Hymenoptera, Vespidae) - Machado, Vera Lígia Letízio [UNESP] (Sociedade Brasileira de Zoologia, 1983)
The data suggest that Polybia (Myrapetra) paulista colonies are established by means of swarm formation having the existence of an initial polygyny and a pleometrose being proved. The reproductive forms are produced once a year (at the start of the year); however, the colonies can last for two or three years. The observations evidenced that the duration of a development period is about 100 days.